Development of Optimization Algorithms for Transportation Problems with Capacity Constraints - Peranginangin, Andreas Perdamenta (Jurnal Info Sains : Informatika dan Sains, 2024)
Transportation movements in urban areas often compete for road space with other users. Inappropriate selection of transportation routes between origin and destination pairs for goods travel results in increased transportation costs. The main goal for transport operators and road users, other than transport, is to minimize travel costs. This research aims to investigate road sections that can be used for transportation at minimum costs for all origin-destination pairs of goods involved in the road transportation network system to form an optimum transportation network design. The optimization objective is to maximize the difference in total transportation costs of the transportation network system between existing conditions and conditions after optimization. A mathematical model is used to represent road user traffic behavior. The optimization process consists of two stages of activity, referred to as bi-level programming: the lower level and the upper level. The lower level provides information about road user behavior on the road section, as demonstrated in the traffic loading process. The user equilibrium traffic loading with diagonalization is used as the solution technique. The upper level employs the GA-I solution technique, which is a genetic algorithm with additional operators. The research presents a method for optimizing urban transportation networks using GA-I. The method is significantly robust and provides an optimum solution in a short time on a hypothetical network.